Education management and management science - International Conference on Education Management and Management Science (ICEMMS); Zheng, Dawei (Computer scientist) (IRAICS Proceedings, 2015)
This proceedings volume contains selected papers presented at the 2014 International Conference on Education Management and Management Science (ICEMMS 2014), held August 7-8, 2014, in Tianjin, China. The objective of ICEMMS2014 is to provide a platform for researchers, engineers, academicians as well as industrial professionals from all over the world to present their research results and development activities in Education Management and Management Science.
Keywords: Educational change -- Congresses; Leadership -- Congresses; School management and organization -- Congresses; Social change -- Congresses; Theory & Practice of Education; Education; Social Sciences